2019
DOI: 10.2147/ppa.s203775
|View full text |Cite
|
Sign up to set email alerts
|

<p>From drug-delivery device to disease management tool: a study of preferences for enhanced features in next-generation self-injection devices</p>

Abstract: Purpose To quantify rheumatology patient preferences and willingness to pay (WTP) for features differentiating enhanced from standard self-injection devices and to investigate differences among subgroups. Patients and methods Patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and axial spondyloarthritis (axSpA) were recruited in the UK. A discrete-choice experiment was used to elicit preferences; respondents were presented with 10 choices between 3 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…It should be noted that not all patients preferred the e-Device over their previous self-injection device. This suggests differences in the self-injection device features required and/or preferred by individual patients and supports previous research that found different patients place different values on the features of self-injection devices [25]. For example, previous research has suggested patients who prefer using a PFS over a PFP find it easier to control the self-injection process with a syringe [26].…”
Section: Discussionsupporting
confidence: 81%
“…It should be noted that not all patients preferred the e-Device over their previous self-injection device. This suggests differences in the self-injection device features required and/or preferred by individual patients and supports previous research that found different patients place different values on the features of self-injection devices [25]. For example, previous research has suggested patients who prefer using a PFS over a PFP find it easier to control the self-injection process with a syringe [26].…”
Section: Discussionsupporting
confidence: 81%
“…The findings of this study are consistent with several previous studies 19 , 26–30 in patients with rheumatic diseases about their preferred attributes in self-injection devices. For instance, Boeri et al found that injection speed control and injection reminders were preferred features for RA patients when selecting self-injection devices.…”
Section: Discussionsupporting
confidence: 93%
“…The benefits of quantifying the monetary benefits of health interventions in this way, even in 'free at the point of use' health care systems such as the UK's NHS, have been explored previously (e.g. Boeri et al, 2019;Ikenwilo et al, 2018;Porteous et al, 2016;Scalone et al, 2011).…”
Section: Survey Developmentmentioning
confidence: 99%